Muslim alternative dispute resolution: Tracing the pathways of Islamic legal practice between south Asia and contemporary Britain - Jones, J (Taylor & Francis (Routledge), 2020)
In recent decades, a wide array of alternative dispute resolution (ADR) forums have taken shape within British Muslim communities. Exploring the development of Muslim ADR practices in contemporary Britain, this paper argues that these quasi-legal mechanisms are not entirely novel formations created afresh in the modern British socio-legal context; but rather, they have antecedents in long-standing cultural and religious norms that can be traced back to colonial-era South Asia. In the Indian subcontinent under British rule, the paper suggests, religious and community leaders often sanctioned the practice of community-led dispute resolution, grounded in Islamic principles of mediation and arbitration, to settle disputes without recourse to government courts. Ultimately, the routines of Muslim non-state adjudication formulated in South Asia were transposed through the dynamics of migration to the UK, where they continue to be visible in faith-based dispute resolution forums and practices.